Low vision devices - Arya, SK; Kalia, A; Pant, K; Sood, S (Nepalese Journal of Ophthalmology, 2010)
A person with low vision has some useful sight. However, low vision usually interferes with the performance of daily activities such as reading or driving. Because low vision cannot be improved by mere traditional methods (i.e., the use of eyeglasses, contact lenses, etc), persons with low vision often rely on the use of a number of different instruments, called low vision devices, and tailored equipment for improved vision. Low vision devices are described in this article. DOI: 10.3126/nepjoph.v2i1.3710 Nep J Oph 2010;2(1) 74-77